Aesthetic Reception of the Qur'an on the Ayaatcontest Account on Instagram (Karl Mannheim's Sociology of Knowledge Perspective) - Nurun Najmatul Ulya; Ahmad Yasir Amrulloh; Ahmad Danish Hakimi bin Shufiady (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2025)
The development of social media also develops new actors and practices in socio-cultural phenomena, including the reception of the Qur’an. This study aims to dig deeper into the aesthetic reception of the Ayaatcontest Instagram account through the perspective of Karl Mannheim's Sociology of Knowledge, who formulates three meanings of human behavior, namely objective, expressive and documentary meanings. By using the netnographic research method, this study draws the conclusion that the meaning of the reception of the Qur’an in the Ayaatcontest account is formed by the organizers and participants. The objective meaning of the organizers is that the social space of the UAE country which is in the Middle East has a passion for preserving the art of Islamic calligraphy or khat, the expressive meaning in the form of selected verses of the Qur'an are verses related to tauhid and social verses, as well as prizes worth 12,000 UAE dirhams, and the documentary meaning as an ongoing effort to maintain the Arabian Peninsula as a 'home' for khat art. While the objective meaning of the participant’s is the process of learning khat which has been carried out for a long time so that they are used to participating in khat competitions. The expressive meaning is the various styles of khat used, starting from Naskhi, Ta'liq, Tsuluts, Diwani, Kufi, and so on, and the meaning of the participant's documentary is the preservation of khat art, as well as existence and self-branding in the world of khat writing, both in social media and in the social sphere of society.